International law issues arising out of Israel's military attack against Lebanon in 2006 - Eishan Jan, Mohammad Naqib (Serials Publications, 2007)
The 2006 Israel's military attack on Lebanon raises numerous issues concerning 'jus ad bellum' and 'jus in bello' rules of international law relating to international armed conflict. Jus ad bellum or the law relating to the initiation of war is now regulated by the Charter of the United Nation (UN). The UN Charter prohibits the use of military force in international relations, with two exceptions: (1) military force may be used in self-defence undcer Article 51 and (2) it may also be used if it is authorized under Chapter VII of the UN Charter. The question to be determined here is whether the 2006 military use force by Israel against Lebanon falls within the ambit of general prohibition of the use of force or within anyone of the two exceptions? Surely, the attack by Israel does not fall within the ambit of the second exception as the UN Security Council did not authorize it, but does this attack falls within the ambit of the first exception under Article 51 of the UN Charter? Israel could invoke its right of self-defence under Article 51 if it was under actual armed attack by Lebanon. The question here is: Did Lebanon attack Israel?If the answer is no, then on what basis Israel could justify its military attack on Lebanon? Can a mere 'border incident', like the 12 July 2006 raid by Hizbollah, entitle Israel to invoke its right of self-defence? What are the requirements for the exercise of the right of self-defence under Article 51? Are these requirements fulfilled by Israel? If the requirements of Article 51 are not fulfilled, which are not, as this paper will explain, can the act of Israel be said to fall within the general prohibition of the use of force under Article 2(4)of the UN Charter? If the answer to the last question is yes then Israel could also be held responsible for the breach of jus ad bellum. Israel would also be responsible if it had failed to abide by the jus in bello rules or rules of international humanitarian law (IHL) which apply to an armed conflict, irrespective of whether it is initiated legitimately or otherwise. Did Israel abide by its obligation under the IHL? Did it use proportionate force? It is not true that Israel acted indiscriminately, without any kind of distinction between 'combatants' and 'non-combatants'? It is not true that Israel targeted civilians and civilian installations? If it is true, which surely it is, as this paper will explain, can then Israel be held responsible to make 'reparation' to the victims of its wrongful conduct? What about the responsibility of those Israeli individuals who were behind the 'grave breaches' of IHL as contains in the four Geneva Conventions of 1949? Are 'grave breaches' of the 1949 Geneva Conventions 'war crimes'? If it is so, which surly it is, then why can the perpetrators of such a crime go unpunished? This paper attempts to discuss these with reference the appropriate provisions of the UN Charter, the 1949 Geneva Conventions, customary international law and decisions of the international courts and tribunals. The Draft Articles on Responsibility of States for Internationally Wrongful Acts 2001 is also referred to discuss the responsibility of Israel for its wrongful conduct. The paper concludes that Israel is responsible for the breach of both 'jus ad bellum' and 'jus in bello' rules of international law relating to armed conflict. Israel itself is bound to make reparation for the victims of its internationally wrongful conduct while Israeli military personals, irrespective of their rank or position, if involved, directly or indirectly, in the commission of war crimes, are criminally responsible. Under the 'command responsibility' doctrine those individuals who did not actually participate in the commission of war crimes but they nevertheless had the power to prevent or punish the criminals and yet fail to do so, they too can be charged for war crimes.